2009
DOI: 10.1111/j.1476-5381.2009.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA protects against sudden cardiac death induced by lethal arrhythmias via repression of microRNA‐1

Abstract: Background and purpose: Tanshinone IIA is an active component of a traditional Chinese medicine based on Salvia miltiorrhiza, which reduces sudden cardiac death by suppressing ischaemic arrhythmias. However, the mechanisms underlying the anti-arrhythmic effects remain unclear. Experimental approach: A model of myocardial infarction (MI) in rats by ligating the left anterior descending coronary artery was used. Tanshinone IIA or quinidine was given daily, before (7 days) and after (3 months) MI; cardiac electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…Undoubtedly all these data supported that the structural and functional protection of LBPs on Tg mouse hearts was due largely to the down‐regulation of miR‐1 level and subsequent restoration of target proteins essential for cardiac contractile function. Other studies found that tanshinone IIA, an active component of a traditional Chinese medicine based on Salvia Miltiorrhiza, protected against arrhythmogenesis after myocardial infarction and cardiac sudden death induced by lethal arrhythmias via repression of miR‐1,8, 13 and Propranolol exerted ischaemic cardioprotection related to down‐regulation of miR‐1,7 providing powerful supports for our cardioprotective result of LBPs on HF by down‐regulation of miR‐1. These findings not only help us understand the mechanisms underlying the beneficial effects of LBPs on HF, but also conceptually advance our view regarding miRNAs to serve as potential therapeutic drug targets.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Undoubtedly all these data supported that the structural and functional protection of LBPs on Tg mouse hearts was due largely to the down‐regulation of miR‐1 level and subsequent restoration of target proteins essential for cardiac contractile function. Other studies found that tanshinone IIA, an active component of a traditional Chinese medicine based on Salvia Miltiorrhiza, protected against arrhythmogenesis after myocardial infarction and cardiac sudden death induced by lethal arrhythmias via repression of miR‐1,8, 13 and Propranolol exerted ischaemic cardioprotection related to down‐regulation of miR‐1,7 providing powerful supports for our cardioprotective result of LBPs on HF by down‐regulation of miR‐1. These findings not only help us understand the mechanisms underlying the beneficial effects of LBPs on HF, but also conceptually advance our view regarding miRNAs to serve as potential therapeutic drug targets.…”
Section: Discussionmentioning
confidence: 71%
“…Increasing lines of evidence have been rapidly evolving for the crucial roles of miRNAs in regulating diverse aspects of cardiac function and progression of HF 4, 5. And notably microRNA‐1 (miR‐1), a cardiac‐enriched miRNA, is in most close relation to heart conditions, and the changes in its expression have been discovered in a variety of heart diseases 6, 7, 8, 9, 10. Our previous report revealed that outcomes of miR‐1 overexpression induced adverse structural remodelling, which impaired cardiac contractile and diastolic function and even caused HF 11.…”
Section: Introductionmentioning
confidence: 99%
“…Deep sequencing of miRNAs from heart tissue has revealed that the abundance of miR-1 accounts for 40 % of all miRNAs. MiR-1 is involved in cardiac development and apoptosis and is elevated in the hearts of individuals with coronary artery diseases, ischemic arrhythmias, and heart failure (Ai et al 2010;Shan et al 2009;Lu et al 2009;Anderson and Mohler 2007;Yang et al 2007). Several studies have shown that miR-1 plays an important role in the regulation of cardiomyocyte apoptosis through post-transcriptional repression of signal proteins, such as Bcl-2 and IGF-1 (Tang et al 2009;Yu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, upregulation of microRNA-1 (miR-1) and consequent reduction of Kir2.1 is observed in rat ventricular myocytes in a rodent model of MI. This is due to the increase in serum response factor (SFR), a transcriptional activator of the miR-1 gene [8].…”
mentioning
confidence: 99%
“…For example, upregulation of microRNA-1 (miR-1) and consequent reduction of Kir2.1 is observed in rat ventricular myocytes in a rodent model of MI. This is due to the increase in serum response factor (SFR), a transcriptional activator of the miR-1 gene [8].In the current issue of Cardiovascular Drugs and Therapy, Li et al report evidence for kinase-dependent modulation of IK1 in an MI rodent model [9]. This work not only identifies a new potential target to attenuate the risk of heart failure after MI, but also provides additional information on the mechanisms of how valsartan, an angiotensin II type I receptor blocker attenuates the effect of MI.…”
mentioning
confidence: 99%